Influence of Community-Led Total Sanitation and Water Coverages in the Control of Cholera in Madarounfa, Niger (2018) - Graveleau, Julien; Reserva, Maria Eleanor; Keita, Alama; Molinari, Roberto; Constantin De Magny, Guillaume (Frontiers in Public Health, 2021)
Every year cholera affects 1.3 to 4.0 million people worldwide with a particularly high presence in Africa. Based on recent studies, effective targeting interventions in hotspots could eliminate up to 50% of cases in Sub-Saharan Africa (1). Those interventions include Water, Sanitation and Hygiene (WASH) programs whose influence on cholera control, up to present, has been poorly quantified. Among the few studies available, D’Mello-Guyett et al. (2020) underline how the distribution of hygiene kits is a promising form of intervention for cholera control and that the integration of a WASH intervention at the point of admission of suspected cases is new in cholera control efforts, particularly in outbreaks and complex emergencies (2). Considering the limited number of studies on Community-Led Total Sanitation (CLTS) and water coverages related to cholera control, the aim of our work is to determine whether these interventions in cholera hotspots (geographic areas vulnerable to disease transmission) have significant impact on cholera transmission. In this study, we consider data collected on 125 villages of the Madarounfa district (Niger) during the 2018 cholera outbreak. Using a hurdle model, our findings show that full access to improved sanitation significantly decreases the likelihood of cholera by 91% (P<0.0001) compared to villages no access to sanitation at all. Considering only the villages affected by cholera in the studied area, cholera cases decrease by a factor of 4.3 in those villages where there is partial access to at least quality water sources, while full access to improved water sources decrease the cholera cases by a factor of 6.3 when compared to villages without access to water (P<0.001). In addition, villages without access to safe water and sanitation are 6.7 times (P<0.0001) more likely to get cholera. Alternatively, villages with full sanitation and water coverage are 9.1 (P < 0.0001) less likely to get cholera. The findings of our study suggest that significant access to improved water and sanitation at the village level offer a strong barrier against cholera transmission. However, it requires full CLTS coverage of the village to observe strong impact on cholera as partial access only has a limited impact.